Characteristics of Peripheral Lymphocyte Subset Alteration in COVID-19 Pneumonia. (30th March 2020) - Wang, Fan; Nie, Jiayan; Wang, Haizhou; Zhao, Qiu; Xiong, Yong; Deng, Liping; Song, Shihui; Ma, Zhiyong; Mo, Pingzheng; Zhang, Yongxi
Abstract: Background: In December 2019, novel coronavirus (SARS-CoV-2) pneumonia (COVID-19) was reported in Wuhan and has since rapidly spread throughout China. We aimed to clarify the characteristics and clinical significance of peripheral lymphocyte subset alteration in COVID-19. Methods: The levels of peripheral lymphocyte subsets were measured by flow cytometry in 60 hospitalized COVID-19 patients before and after treatment, and their association with clinical characteristics and treatment efficacy was analyzed. Results: Total lymphocytes, CD4 + T cells, CD8 + T cells, B cells, and natural killer (NK) cells decreased in COVID-19 patients, and severe cases had a lower level than mild cases. The subsets showed a significant association with inflammatory status in COVID-19, especially CD8 + T cells and CD4 + /CD8 + ratio. After treatment, 37 patients (67%) showed clinical response, with an increase in CD8 + T cells and B cells. No significant change in any subset was detected in nonresponsive cases. In multivariate analysis, posttreatment decrease in CD8 + T cells and B cells and increase in CD4 + /CD8 + ratio were indicated as independent predictors of poor efficacy. Conclusions: Peripheral lymphocyte subset alteration was associated with clinical characteristics and treatment efficacy of COVID-19. CD8 + T cells tended to be an independent predictor for COVID-19 severity and treatment efficacy. Abstract : Peripheral lymphocyte subset alteration showed a clear association with the clinical characteristics of COVID-19, especially in relation to disease severity assessment and treatment efficacy prediction, which could help to indicate timely interventions to be provided by physicians.